2012
DOI: 10.1158/0008-5472.can-11-4204
|View full text |Cite
|
Sign up to set email alerts
|

BCL2 Suppresses PARP1 Function and Nonapoptotic Cell Death

Abstract: BCL2 suppresses apoptosis by binding the BH3 domain of pro-apoptotic factors and thereby regulating outer mitochondrial membrane permeabilization. Many tumor types, including B-cell lymphomas and chronic lymphocytic leukemia, are dependent on BCL2 for survival, but become resistant to apoptosis after treatment. Here we identified a direct interaction between the anti-apoptotic protein BCL2 and the enzyme poly(ADP) ribose polymerase 1 (PARP1), which suppresses PARP1 enzymatic activity and inhibits PARP1-depende… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…However, high levels of BCL2 expression block apoptosis, allowing the tumor cells to survive. This conclusion is supported by the observation that anti-BCL2 therapy (ABT-737) induced characteristics of apoptosis in vitro when applied in conjunction with the topoisomerase II poison etoposide [11]. An association between low levels of BCL2 expression and an enhanced anthracycline response (pCR) in neoadjuvant settings has also been reported by others [13,15,32].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, high levels of BCL2 expression block apoptosis, allowing the tumor cells to survive. This conclusion is supported by the observation that anti-BCL2 therapy (ABT-737) induced characteristics of apoptosis in vitro when applied in conjunction with the topoisomerase II poison etoposide [11]. An association between low levels of BCL2 expression and an enhanced anthracycline response (pCR) in neoadjuvant settings has also been reported by others [13,15,32].…”
Section: Discussionmentioning
confidence: 67%
“…It also performs other functions, such as promoting cell growth and proliferation [9][10][11]. Preclinical data showed that BCL2 expression was associated with resistance to anthracycline doxorubicin [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that Bcl-2 has multiple functions, including regulation of calcium homeostasis and mitochondrial dynamics, as well as suppression of nonapoptotic cell death, suggesting that various functions of Bcl-2 are involved in the attenuation of doxorubicin-induced cell toxicity of luteolin. 32,33) Our findings indicate that luteolin attenuates the pharmacological action of doxorubicin in MCF-7 cells, depending on the experimental conditions.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, Dutta et al [66] have demonstrated that Bcl-2 may influence PARP activity both in vitro and in cancer cells by a direct interaction with PARP-1. The overall relationship between PARP-1 and Bcl-2 may depend on the various inner environment of different cell lines and on the pathological condition.…”
Section: Discussionmentioning
confidence: 99%